Thinking Out of the Box: On the Ability of Zea mays L. to Biotrasform Aflatoxin B1 Into Its Modified Forms - Righetti, Laura; Rolli, Enrico; Dellafiora, Luca; Galaverna, Gianni; Suman, Michele; Bruni, Renato; Dall’Asta, Chiara (Frontiers in Plant Science, 2021)
While aflatoxin metabolism in animals has been clarified, very limited information is so far available on the possible biotransformation occurring in plants. Therefore, this work aimed at investigating whether AFB1 metabolites could occur in field-grown infected maize and the putative role of Zea mays L. metabolism in their production. For such scope, asymptomatic in vitro grown plantlets and in silico evaluations of plant transforming enzymes were used to pinpoint how plants may handle these compounds. Our data demonstrated the role of maize plants in the production of Phase I hydroxylated aflatoxins, including among others, AFM1, AFM2, and aflatoxicol, and suggested that plant cytochromes may be involved in this biotransformation of AFB1.